Mathematics
PixelStorm
22

Use f (x) and g (x) to evaluate each expression symbolically. f (x)=4x-x^3, g (x)=x+3 (A) (g+g)(-2) (B) (f-g)(0) (C) (gf)(1) (D) (g/f)(-3)

+2
(1) Answers
Carry751

 f(x) = -x³ + 4x g(x) = x + 3 A. (g + g)(-2) = (-2 + 3) + (-2 + 3)     (g + g)(-2) = 1 + 1     (g + g)(-2) = 2 B. (f - g)(0) = (-(0)³ + 4(0)) - (0 + 3)     (f - g)(0) = (0 + 0) - 3     (f - g)(0) = 0 - 3     (f - g)(0) = -3 C. (g · f)(1) = (1 + 3)(-(1)³ + 4(1))     (g · f)(1) = (4)(-1 + 4)     (g · f)(1) = (4)(3)     (g · f)(1) = 12 D. (g/f)(-3) = (-3 + 3)/(-(-3)³ + 4(-3))     (g/f)(-3) = 0/(-(-27) - 12)     (g/f)(-3) = 0/(27 - 12)     (g/f)(-3) = 0/15     (g/f)(-3) = 0

Add answer